POLA ASUH ORANG TUA DALAM PERILAKU SOSIAL GENERASI MILLENIAL DITINJAU DARI NEUROSAINS - Taufiq Ziaul Haq (LPPM Institut Pesantren KH. Abdul Chalim, 2020)
Parenting in the social behavior of millennial generation in terms of neuroscience. Millennials are the generation born when technology has emerged and started to develop. In this generation we can find several inherent characters. The inherent character of this millennial era is that besides being addicted to the internet, self-confidence is high, more insightful, and more tolerant of change. Millennials have better education than Baby Boomers, because they are quite familiar with technology. The life of the millennial generation cannot be separated from technology, especially the internet and entertainment, which has become a basic need for this generation. In this generation the accuracy of parenting and education applied is very influential on emotional stability. Emotional stability is not only an effective picture in a person's personality pattern but also helps in controlling a person's growth and development with a continuous process through feelings for emotional health from within and within the environment. In this journal study also reveals the performance of the brain that manages and processes emotions. The emotional process in humans is carried out by the brain which is directly related to emotions, namely the amygdala, the amygdala is the main component producing emotions. The amygdala part of telencephalon which is located in the temporal lobe which functions for memory, emotions and fear. The parenting style applied by parents in the millennial era can influence children's social behavior. The development of children's social behavioral abilities in the millennial era can be done by habituating and interacting with their environment. A person who has good social skills can be seen through the way children socialize well in their environment.